Influence of sociodemographic factors on quality of life in women living in Lublin Province in Poland - Żołnierczuk-Kieliszek, Dorota; Kulik, Teresa B.; Janiszewska, Mariola; Stefanowicz, Agata (Menopause Review/Przegląd Menopauzalny, 2014)
The aim of the study is to evaluate the impact of sociodemographic factors on the quality of life (QOL) in 45-65-year-old women. Material and methods : The research by means of a survey method, postal questionnaire technique, comprised 2143 women – a representative sample of the female population living in Lublin Province. Three standardized questionnaires – WHOQOL-BREF, Women’s Health Questionnaire and SF-36 – as well as an original questionnaire were used as research tools. In statistical analysis Student’s t-test for two groups, an analysis of variance, Dunnett’s T3 test for multiple comparisons, a one-way analysis of variance (one-way ANOVA) and a stepwise logistic regression analysis were used. Results : In the population of peri- and postmenopausal women a significantly better quality of life in comparison with the rest of the studied women was established in women aged 45-49 years, respondents living permanently in urban areas as well as better educated women, those with full-time employment, especially those doing intellectual work, women remaining in a long-lasting relationship, and women assessing their financial situation and living conditions as well. Logistic regression analysis showed that the strong predictors of poor quality of life were as follows: self-assessment of living conditions as poor, self-assessment of financial situation as poor, permanent place of residence in the country, lower education level (incomplete primary education, primary education). Conclusions : The group of women with worse quality of life should become the main addressee of preventive programmes and health policy programmes designed for peri- and postmenopausal women.